Smell Status in Children Infected with SARS‐CoV‐2. (18th January 2021) - Rusetsky, Yury; Meytel, Irina; Mokoyan, Zhanna; Fisenko, Andrey; Babayan, Anna; Malyavina, Ulyana
Abstract : Objectives/Hypothesis: This study aimed to evaluate the olfactory status in children with laboratory confirmed SARS‐CoV‐2 using subjective and psychophysical methods. Study Design: Prospective clinical cross‐sectional study. Methods: This is a prospective clinical cross‐sectional study of 79 children with COVID‐19. The 21st item of SNOT‐22 questionnaire and odor identification test were used for smell assessment. Children were examined twice during the hospitalization, and a telephone survey was conducted 60 days after hospital discharge. Results: Immediately after confirmation of COVID‐19, smell impairment was detected in 86.1% of children by means of the Identification test and in 68.4% of children by means of the survey ( P = .010). After 5 days survey revealed a statistically significant decrease in the number of patients with hyposmia (41 out of 79, 51.9%). On the first visit, the mean Identification test score corresponded to "hyposmia" (9.5 ± 2.7), while on the second visit, the average value was 13.1 ± 1.9, which corresponded to "normosmia." According to the telephone survey, recovery of the olfactory function occurred within 10 days in 37 of 52 patients (71.2%), 11 to 29 days ‐ in 12 children (23.1%), and later than 30 days ‐ in three cases (5.7%). Conclusions: In the pediatric population, olfactory dysfunction is an early and common symptom of COVID‐19. There is a trend to quick recovery of olfactory function in children with COVID‐19. The overwhelming majority of patients (94.3%) had no subjective olfactory complaints by the end of the first month. Level of Evidence: 4 Laryngoscope, 131:E2475–E2480, 2021